International Architecture News (project baikal, 2021)
The news section presents the winners of The Daylight Award 2020 and The Kaira Looro Competition, and announces the theme of The 2A Continental Architectural Awards 2020, which will be conducted virtually this year.
Keywords: Daylight Award; 2ACAA; Kaira Looro; international architecture competition